Cost effectiveness analysis of universal varicella vaccination in the Russian Federation - A. V. Rudakova; S. M. Kharit; I. V. Babachenko; L. N. Konovalova; S. V. Rychkova; A. N. Uskov; Yu. V. Lobzin (Журнал инфектологии, 2021)
Varicella is a significant burden on society and the healthcare system.Objective: to analyze the cost effectiveness of universal vaccination of children against varicella.Material and methods. The analysis was carried out from the perspective of the healthcare system and societal perspective, based on epidemiological data for the Russian Federation. The effect was taken into account only in the vaccinated population. The time horizon of the study is 10 years. The amount of direct medical costs for treatment of varicella was calculated based on the rates of compulsory medical insurance in St. Petersburg in 2020. The cost of drug therapy in outpatient settings was calculated based on the weighted average retail price of prescribed drugs. The analysis of direct nonmedical and indirect costs was carried out taking into account statistical data on the Russian Federation and duration of temporary disability of family members of sick children. Costs and quality-adjusted life expectancy were discounted by 3.5% per year.Results. The average cost due to the disease in the Russian Federation is 43,139 rubles / patient, of which 8,5% is direct cost. Vaccination of 100,000 children will prevent 38,551 cases of varicella in 10 years. When analyzing from a social perspective, vaccination provides a reduction in costs compared to no vaccination, and the savings will amount to 10.1 thousand rubles per 1 vaccinated person.If vaccination coverage is 90%, taking into account the fact that the cohort of children in the Russian Federation at the age of 1 year is about 1.9 million people, the cost of vaccination will amount to about 8.1 billion rubles annually. At the same time, already 6 years after vaccination, the volume of averted budgetary costs will exceed the costs of vaccination.Conclusion. Universal varicella vaccination of children will reduce the incidence of the disease and reduce the budget costs associated with this disease.